Collaborative Transformation of Teachers and Principals in Strengthening the Quality of Science Learning in Elementary Schools - Mulyadin Mulyadin; Desak Putu Paramiti; Nyoman Dantes (Prodi PAI STIT Sunan Giri Bima, 2026)
This study aims to analyze the collaborative transformation between teachers and principals in strengthening the quality of Natural Science (IPA) learning in elementary schools through a qualitative literature study approach. Educational collaboration is not only understood as technical cooperation, but also as a transformational process involving paradigm shifts, participatory leadership, and a culture of continuous learning in the school environment. This research method uses a literature study approach by analyzing various scientific sources, such as reputable journals, academic books, and national education policy documents. The results of the study indicate that collaborative transformation between teachers and principals plays a significant role in improving the quality of science learning through strengthening pedagogical competence, methodological innovation, and visionary collaborative leadership. This transformation takes place through three main dimensions: structural, cultural, and pedagogical transformation. First, in the structural dimension, principals reform the learning management system to be more participatory, by involving teachers in strategic decision-making, curriculum planning, and evaluation of learning outcomes. Second, in the cultural dimension, collaboration is transformed into a school culture that fosters mutual trust, openness, and a commitment to quality learning. The principal acts as a catalyst for change, fostering reflective, innovative, and collaborative values within the school environment. Third, in the pedagogical dimension, collaboration generates innovation in science learning practices.